Contribution to the Effectiveness and Efficiency of Kota Pari Village Communities in Increasing Sustainable Economic Growth and Creative Industry - Suwarno, Suwarno; Darmilisani, Darmilisani; Siregar, Mira Yosefa; Selviani, Putri (Universitas Negeri Medan, 2023)
The research team at Kota Pari Village, Pantai Cermin District, Serdang Bedagai Regency set out to answer the question,